The music of thought in the poetry of George Oppen and William Bronk - Weinfield, Henry (Iowa City : University of Iowa Press, 2009)
From his careful readings of George Oppen's and William Bronk's poetry to his fascinating examination of the letters they exchanged, Weinfield provides important aesthetic, epistemological, and historical insights into their poetry and poetic careers. In bringing together for the first time the work of two of the most important poets of the postwar generation, The Music of Thought not only illuminates their poetry but also raises important questions about American literary history and the categories in terms of which it has generally been interpreted.
Oppen, Bronk, and the story behind "a narrative" -- Because the known and the unknown touch : a reading of Oppen's "Of being numerous" -- In the drift of the world : a reading of Bronk's Life supports: new and collected poems -- Oppen's reoccupation of traditional lyric in "Eclogue," "Psalm," and "Ballad."
Includes bibliographical references (pages 223-229) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Oppen, George -- Criticism and interpretation; Bronk, William -- Criticism and interpretation; Bronk, William; Oppen, George; American poetry -- 20th century -- History and criticism; Poésie américaine -- 20e siècle -- Histoire et critique; POETRY -- American -- General; LITERARY CRITICISM -- Poetry; American poetry; 1900-1999; Criticism, interpretation, etc